2006
DOI: 10.1261/rna.128906
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary rates of transition metal ion-mediated ribozyme catalysis

Abstract: In pre-steady-state, fast-quench kinetic analysis, the tertiary-stabilized hammerhead ribozyme ''RzB'' cleaves its substrate RNA with maximal measured k obs values of ; ;3000 min À1 in 1 mM Mn 2+ and ; ;780 min À1 in 1 mM Mg 2+ at 37°C (pH 7.4). Apparent pKa for the catalytic general base is ; ;7.8-8.5, independent of the corresponding metal hydrate pKa, suggesting potential involvement of a nucleobase as general base as suggested previously from nucleobase substitution studies. The pH-rate profile is bell-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
102
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 35 publications
17
102
0
1
Order By: Relevance
“…Moreover, the mechanistic model for metal ion binding proposed here that involves interaction with 2′OH of G8, is consistent with kinetic analysis indicating that the pK a of the general acid is down-shifted by around 4-7 pK a units in a metal-dependent manner, correlated with the metal pK a . 59 The simulation results suggest that the Mg 2+ interacts strongly with the 2′OH of G8 in the early TS mimic and could contribute to a significant lowering of the pK a value, and in the late TS mimic the G8 2′OH is hydrogen bonded to the leaving group and poised to act as a general acid catalyst. The Mg 2+ ion may additionally play a direct role in stabilizing the negative charge accumulated in the leaving group in the late TS, and when the proton from the G8 2′OH is ultimately transferred, the coordination of Mg 2+ is positioned to revert back to stabilize the resulting G8 2′-alkoxide.…”
Section: Mechanistic Interpretationmentioning
confidence: 88%
“…Moreover, the mechanistic model for metal ion binding proposed here that involves interaction with 2′OH of G8, is consistent with kinetic analysis indicating that the pK a of the general acid is down-shifted by around 4-7 pK a units in a metal-dependent manner, correlated with the metal pK a . 59 The simulation results suggest that the Mg 2+ interacts strongly with the 2′OH of G8 in the early TS mimic and could contribute to a significant lowering of the pK a value, and in the late TS mimic the G8 2′OH is hydrogen bonded to the leaving group and poised to act as a general acid catalyst. The Mg 2+ ion may additionally play a direct role in stabilizing the negative charge accumulated in the leaving group in the late TS, and when the proton from the G8 2′OH is ultimately transferred, the coordination of Mg 2+ is positioned to revert back to stabilize the resulting G8 2′-alkoxide.…”
Section: Mechanistic Interpretationmentioning
confidence: 88%
“…Indeed, an in vitro selection experiment identified numerous additional tertiary interactions not found in biology which also enhanced the cleavage rate (14). Analysis of one of these indicated that it promoted cleavage hundreds of times faster than minimal hammerheads (15).…”
mentioning
confidence: 99%
“…This leads to reduced solvent exchange rates and increased solvation enthalpy, but at the same time also makes it a most suitable interaction partner for the non-bridging phosphoryl oxygens of the nucleic acid backbone, allowing them to pack particularly closely [51], which is a prerequisite for the physiological folding of large RNAs. In accordance, a nearly perfect correlation between the cleavage rate of the hammerhead ribozyme [52,53] and the metal ion affinity towards phosphate monoesters can be established [34]. Nevertheless, such a correlation cannot be established, for example, for the glmS ribozyme [54], indicating a crucial influence of further ligand sites.…”
Section: Dominance Of Mg 2+mentioning
confidence: 83%
“…Zn 2+ is also very thiophilic and more similar in size to Mg 2+ , but engages in variable coordination geometries [87]. Tl + has been employed as a substitute for K + , making use either of its thiophilicity or of the abundant spin 1/2 nucleus of 205 [52,53] or Ca 2+ in the case of the antigenomic form of the hepatitis delta virus (HDV) ribozyme [88]. While in the case of the two Hammerhead ribozymes, the observed cleavage rates correlate with the respective phosphate affinity of the metal ion applied [34], in the case of the glmS ribozyme, no such correlation is observed [54].…”
Section: Influences Of Metal Ions Other Than Mgmentioning
confidence: 99%